The promise of the West : young pioneers on the Overland Trails - O'Brien, Mary Barmeyer (TwoDot, 2015)
"Driven by the promise of prosperity and opportunity on the frontier, thousands of men and women traveled west in the mid-1800s to forge a new life. Accompanying them were their children, wide-eyed and excited about the adventures that awaited them as they headed toward the setting sun. Little did they know how treacherous and grueling the trip would be"--Provided by publisher